Psychiatric Care, Training and Research in Aotearoa New Zealand - Chao-Cheng (Chris) Lin; Charlotte Mentzel; Maria Luz C. Querubin (Taiwanese Journal of Psychiatry)
Objective: Aotearoa New Zealand, a commonwealth country, is situated in the South Pacific Ocean, in the southwestern most part of Polynesia. The country comprises two main islands – the North and South Islands – with total population of 5 million. Within this context, the authors describe mental health (including indigenous Māori perspective), psychiatrist training, mental healthcare system, and recent research in New Zealand. This review is intended to familiarize the readers of the Taiwanese Journal of Psychiatry with the current status of psychiatric practice in New Zealand. Methods: The authors of this review collected and reviewed relevant literature on psychiatric care, education, training, and research in New Zealand. In addition, official government publications, such as reports from the Stats New Zealand and Ministry of Health, were examined to gather relevant data. Results: After providing a brief overview of New Zealand’s geography and history, the authors describe two major ethnic groups, New Zealanders of European descents, and the Māori, who are descendants of Polynesian settlers. Then, the prevalence of psychiatric diseases, trainings for the psychiatrist workforce, the Royal Australian and New Zealand College of Psychiatrists, the New Zealand Mental Health Act, and recent psychiatric research are highlighted. Conclusion: New Zealand, with dominant European and Māori cultural groups and an emerging Asian population, has a growing, diverse population. Its universal healthcare system, restructured in 2022 under Te Whatu Ora (Health New Zealand) is aimed at enhancing efficiency and equity but faces challenges like Māori underrepresentation in the psychiatry workforce and rising demands from the growing Asian community. While mental health issues have gained government attention, future advancements are needed to improve psychiatrist recruitment and retention, enhance equitable service delivery, strengthen mental health laws, and increase psychiatry funding.